Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Media Audio Visual Di Sd Negeri Sumurgung I - Suryaningrum, Renis; Wiratsiwi, Wendri (Universitas Pakuan, 2025)
This study aims to utilize audiovisual media to improve mathematics learning outcomes of second-grade students on the sub-material of patterns around us at UPT SD Negeri Sumurgung I Tuban. This study uses a type of classroom action research (CAR). Nine students in grade II of UPT SD Negeri Sumurgung I Tuban became the subjects of this study. Planning, implementation, observation, and analysis are two phases that form the research process. Observation sheets and tests are one of the tools used. Data were analyzed using percentages. This study resulted in that the mathematics scores of sub-material patterns around us of second-grade students at UPT SD Negeri Sumurgung I can be increased by utilizing audiovisual media. The classical completion rate increased from 55.6% in the first cycle to 89% in the second cycle. Thus, audiovisual media can help second-grade students at UPT SD Negeri Sumurgung I to improve mathematics learning outcomes of sub-material patterns around us.